The inherent benefit of monetary unions - Dominik Groll; Tommaso Monacelli (Journal of Monetary Economics, 2020)
If the monetary authority lacks commitment, a monetary union can dominate flexible exchange rates. With forward-looking staggered pricing, inertia in the terms of trade—induced by a fixed exchange rate—is a benefit under discretion, since it acts like a commitment device. By trading off flexibility in the adjustment of the terms of trade, the monetary authority improves on its ability to manage private sector's expectations. The higher the incidence of asymmetric inefficient shocks, and/or the higher the degree of nominal price rigidity, the greater the inherent benefit of monetary unions, in stark contrast to the traditional optimum currency area theory.
Keywords: 330